The First Exhibitions in Marc Chagall’s Creative Biography - Lisovs, Aleksandrs (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2015)
This article focuses on the early exposition experience of Marc Chagall, on his participation in Russian exhibitions in 1910-12. This experience had influenced his formation as a professional artist. This experience resulted in the recognition, defined his relationship with the artistic environment, critics and collectors. Two letters of M. Chagall to M. Dobuzhynski are published in original language. They are the convincing proof of the fact that at an initial stage of his formation during the first Parisian period when Chagall wasn’t still known and recognized, he continued to enjoy support and care of his Petersburg teachers M. Dobuzhynski and L. Bakst, hoping for their help. In the first half a year of his Parisian life he saw the recognition in a circle of Russian artists of the association “World of Art”. The latest Parisian experience furthered the estrangement of M. Chagall from the “World of Art” and created the rapprochement with the leftist artists oriented on P. Cezanne’s system, the association “Bubnovy Valet” (“Jack of Diamonds”).